Analisis Kualitas Layanan Website Sistem Informasi Pelayanan Perizinan Online DPMPTSP Kota Palembang Menggunakan Metode Webqual 4.0 - Andri; Imam Mizan; Edi Supratman; Kiky Wardani (Universitas Mercu Buana Yogyakarta, 2025)
The rapid development of information technology, particularly the internet, has driven governments to adopt e-government to enhance information access, improve service efficiency, and promote administrative transparency. One of its implementations is a public service website that enables citizens to access digital services and information. The success of this system highly depends on the quality of the website in terms of usability, information completeness, and service interaction. This study employs the Webqual method, which consists of Usability Quality, Information Quality, and Interaction Quality, using a quantitative approach to evaluate the website’s service quality. The results indicate that the Online Licensing Service Information System website of DPMPTSP Palembang City has improved service efficiency by accelerating the licensing process in accordance with SOP’s, allowing applicants to obtain their licensing certificates within a maximum of three days. The system implementation has successfully reduced reliance on slower manual processes. However, issues remain regarding accessibility and information updates on PPID, which may hinder transparency. Further analysis reveals that Usability Quality, Information Quality, and Interaction Quality simultaneously have a significant impact on user satisfaction. However, when examined separately, only Information Quality and Interaction Quality show a significant positive impact, while Usability Quality does not strongly influence user satisfaction. The development of public service information systems should focus on improving accessibility, creating a more intuitive interface, and ensuring regular updates of information. With these optimizations, the system can be more effective in meeting user needs and enhancing their experience in accessing government digital services.